Influence of sucrose on structural and mechanical properties of the system based on «jelly forming semi-finished product for jelly products» - Степанова, Тетяна Михайлівна; Кондратюк, Наталія В’ячеславівна; Пивоваров, Євген Павлович (Eastern-European Journal of Enterprise Technologies, 2015)
The effect of sucrose on the jelly formation in systems based on the «Jelly forming semi-finished product for jelly products» was investigated. Chemistry and dehydrating effect of sucrose on the pectin-calcium gel system under conditions of controlled acidity (pH=3±0,2) were described and studied accordingly. The sucrose concentrations, at which gels remain flexible and elastic and have high organoleptic properties were determined. The optimal ratio of components in the low-esterified amidated pectin: eggshell powder: sucrose system, at which the syneresis phenomenon does not appear within the time limit, recommended for storage was found. The results ensure high quality indicators of desserts based on the «Jelly forming semi-finished product for jelly products» that greatly expands the range of low-calorie desserts with significant health effect and increases the number of energy- and resource-saving technologies from domestic raw materials.